*This preview shows
pages
1–2. Sign up
to
view the full content.*

This
** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*
**Unformatted text preview: **r r ( ) = , where = " ! r ( ) = c 2 r 1 " n # r ( ) = c 2 r 2 " n 2 " n + c 3 Setting r ( ) from equation 2 & 3 equal we have: c 1 r 1 ! n 2 = c 2 r 2 ! n 2 ! n + c 3 Setting the exponents on the r term equal we have: 2 ! n = 1 ! n 2 " n = 3 n = 1 also works, since: c 1 r 1 ! 1 2 = c 1 = " r 2 ! 1 2 ! 1 + c 1...

View
Full
Document